Evaluating the Impact of Road Infrastructure on Motor Insurance Claims - Dawodu, Adenrele Wasiu (ESUT JOURNAL OF SOCIAL SCIENCES, 2025)
This study investigated the intricate relationship between road infrastructure conditions and motor insurance claim patterns, drawing empirical evidence from Lagos State, Nigeria. The research aimed to determine the significant relationship between specific road infrastructure deficiencies and the frequency of motor insurance claims, and to evaluate the impact of road infrastructure quality on the severity and cost of these claims in Nigeria. The findings reveal a significant association between road infrastructure deficiencies and higher frequencies of motor insurance claims. The model explained approximately 39.7% of the variation in claim frequency, with potholes, signage, drainage, and intersections being statistically significant predictors. Furthermore, road infrastructure quality significantly impacts the severity and cost of motor insurance claims. The model accounted for 34.8% of the variation in claim severity, with potholes, signage, drainage, intersections, and traffic calming measures all being significant predictors. Notably, improved drainage systems were strongly associated with a reduction in claim severity and cost. The study concludes that poor road infrastructure exacerbates accident incidence and escalates the financial magnitude of insurance claims in Nigeria. These results align with Cramér’s Risk Theory, suggesting that environmental factors significantly alter the risk profile of motor insurance portfolios. The implications for the Nigerian insurance sector are substantial, highlighting the need for integrating spatial risk factors into underwriting models to enhance pricing precision and capital adequacy. The study advocates for urgent and targeted investment in road infrastructure improvements, such as better drainage systems, traffic signage, road lighting, and traffic calming features, to reduce both the frequency and cost of motor insurance claims and foster sustainable road safety progress in Nigeria.